Sentidos da matriz energética brasileira na mídia: projetos hidrelétricos na Amazônia de FHC a Lula (2001-2002 e 2008-2009) - BARROS, Thiago Almeida (Universidade Federal do Pará, 2017)
This work is a content analysis on the debate about the Brazilian hydroelectric energy matrix in the media in two moments of sectorial crisis: first in 2001-2002, on the Fernando Henrique Cardoso’s government, when occurred the blackout and the energy rationing and emergency public policies were included in the PPA; second, in 2008-2009, on the Lula’s government, when it created the impression that the Brazilian energy system would not support the growth of the economy, especially given the threat of future blackouts, which led to the creation of an electrical component in PAC. From the corpus, collected editions of the newspaper O Globo, Folha de S. Paulo and O Estado de S. Paulo in the period, we identified pressure groups and actors mostly occurring in the media sphere and how they legitimize the discourse of clean development and Amazon vocation for big dams like Belo Monte (Pará), São Francisco and Jirau (Rondônia). The groups, linked to industrial and construction sectors, using the media as one more tool to influence the behavior of public opinion and force the government, will eventually repeat business interests.